Mathematical Problem Solving Ability: The Impact of Mathematics Learning Videos on an E-Learning Platform - Salsabila, Aufa; Pradipta, Trisna Roy (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
This study aimed to determine the effect of instructional videos on an e-learning platform toward students' mathematical problem solving ability. This research employed the quantitative aproach and experimental research design. This study utilized a test instrument to determine students' mathematical problem solving abilities. Furthermore, a t-test was performed on the data that had fulfilled the prerequisite testings: the normality test and the homogeneity test. The results indicated that there was an effect of mathematics learning videos on the e-learning platform on students' mathematical problem solving abilities. Students who watched the instructional videos had better mathematical problem solving abilities than students who did not watch the instructional videos.